2018
DOI: 10.3892/or.2018.6482
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor�18 promotes the growth, migration and invasion of MDA‑MB‑231 cells

Abstract: Abstract. Fibroblast growth factor 18 (FGF18) increases cell motility and invasion in colon tumors, and is linked with ovarian and lung tumors. Furthermore, the increased expression of FGF18 mRNA and protein has been associated with poor overall survival in cancer patients. However, its function has not been investigated in breast cancer. In the present study, we demonstrated that FGF18 promoted cell growth and metastasis in vitro and stimulated tumor growth in xenograft models in vivo. FGF18 mediated the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…3 a). Previous studies suggested that the amplification of FGF18 was found in a number of solid tumors, and its overexpression was significantly correlated with poor prognosis [ 21 24 ]. Considering the important roles of both FGF18 and HDAC7 in NSCLC progression, we were interested in investigating their regulatory relationship and underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 a). Previous studies suggested that the amplification of FGF18 was found in a number of solid tumors, and its overexpression was significantly correlated with poor prognosis [ 21 24 ]. Considering the important roles of both FGF18 and HDAC7 in NSCLC progression, we were interested in investigating their regulatory relationship and underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we focused on FGF18, which is involved in HDAC7-mediated NSCLC progression. Previous studies have reported a prominent role of FGF18 in tumorigenesis, proliferation, and metastasis of several tumors, including gastric cancer, ovarian cancer, and breast cancer [ 21 , 22 , 24 ]. Chen et al found that the FGF18 could promote proliferation and migration of large cell lung carcinoma (LCLC) cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, different from human breast cancer, miR-21 had a very high likelihood of targeting to 3′ UTR of the fibroblast growth factor 18 FGF18 (score 97 in miRDB) mRNA. In breast cancer, FGF18 promotes cell proliferation through the ERK/c-Myc signaling pathway and stimulates the production of epithelial-to-mesenchymal transition (EMT) factors, thus, promoting neoplastic cell migration and invasion [ 47 ]. Noteworthy, in the current study, the highest level of miR-21 expression was observed in the two malignant tumors with evidence of neoplastic emboli in lymphatic vessels (i.e., tubular carcinoma, grade III; inflammatory carcinoma, grade III) (Data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…FGF8 signalling increases oestrogen-induced breast cancer cell proliferation by inducing the expression of the ER mRNA, and at the same time suppresses the inhibition of mitosis by activating the cell cycle regulator CDC2 and other regulators of cell cycle entry [ 164 , 165 ]. The increased expression of FGF18 mRNA and protein has been associated with migration in vitro and poor overall survival in cancer patients [ 166 ]. A recent study showed that FGF18 increased cell migration and EMT through AKT signalling and by inducing the transcription of proliferation-related genes, including CDC2 , metastasis-related genes ( TGFβ , MMP-2 and MMP-9 ) and EMT markers like the SNAIL proteins and N -cadherin [ 167 ].…”
Section: Fgfs In Breast Cancermentioning
confidence: 99%